MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS BAGI SISWA/I SDI YAYASAN ANWARUL JAM’IYYAH DI DESA LENGGAHSARI - Fitriyanti, Dea; Danapriatna, Nana; Fakhran Al Ramadhan, Muhammad (An-Nizam, 2023)
In this modern era, technological advancement necessitates individuals to master English as an international language. Therefore, it is imperative for formal education to initiate English language learning from an early age within the classroom, enabling students to easily follow English lessons in junior high school. This study was conducted at SDI Yayasan Anwarul Jam’iyyah with the aim of enhancing students' understanding of English and instilling motivation regarding the importance of learning the language. The applied method was Community Education. The results indicate that students at SDI Yayasan Anwarul Jam’iyyah exhibit high levels of motivation and enthusiasm towards learning English in the classroom. This research contributes significantly to strengthening students' grasp of the English language and paves the way for deeper learning at the secondary school level. Learning English is not only an obligation but also an enjoyable experience for students.